Gen Z and millennial investment intention in Islamic securities crowdfunding - Koeswandana, Noorfaiz Athallah; Octavio, Muhammad Fadhly Rizky (Asian Journal of Islamic Management (AJIM), 2026)
Purpose – This study explores factors influencing the millennial generation's intention to invest in Islamic securities crowdfunding (Islamic SCF) using the theory of planned behavior (TPB) with knowledge about riba as a moderating variable.Methodology – A quantitative approach involving 292 Indonesian millennial respondents was used. Data were collected through structured questionnaires and analyzed using structural equation modeling (SEM) with SmartPLS 3.9 software.Findings – The results confirmed all TPB hypotheses, except for perceived usefulness. Significant relationships were found between attitudes, subjective norms, perceived behavioral control, and investment intentions in Islamic SCF. Knowledge about riba effectively moderated investment decisions among Indonesian millennials.Implications – These findings provide valuable insights for Islamic SCF platforms to understand user behavior and decision-making processes, enabling strategic product development, marketing strategies, and platform enhancement to increase millennial participation.Originality – This study contributes to the limited Islamic Securities Crowdfunding literature by focusing on Indonesian millennials' investment intentions and incorporating riba knowledge as a moderating variable within the TPB framework